Effects and Determinants of Outcomes-Focused Learning Environments - Aldridge, Jill; Fraser, Barry (James Nicholas Publishers, 2011)
A common line of past learning environment research has involved associations between the learning environment and student outcomes (i.e. the effects of learning environment). It is one thing to advocate that teachers establish outcomes-focused learning environments, but it is important to know whether the creation of such learning environments are associated with more positive student attitudes and higher achievement. Consequently, the first aim of this article is to report our investigation of associations between emphases in outcomes-focused classroom learning environments (as assessed by the Technology-Rich Outcomes-Focused Learning Environment Inventory, TROFLEI, and the student outcomes of attitudes and achievement. Because many past learning environment studies focused on determinants of classroom environments, our study of outcomes-focused classroom environments also employed the scales of the TROFLEI as dependent variables in investigating whether differences exist in perceived learning environment, preferred learning environment and attitudes between: (a) males and females and (b) students enrolled in university-entrance examination subjects and wholly school-assessed subjects.